COSTA RICA WITHOUT BORDERS #10 - Aragón-Vargas, Luis Fernando (Escuela de Educación Física y Deportes - Universidad de Costa Rica, 2014)
In this section we publish the Spanish version of abstracts from original articles in other languages, published by researchers from Costa Rican universities in different journals around the world. We include the citation to the original work, together with a brief description about where the study took place. The journals must be peer-reviewed and have a formal editorial board. These abstracts are from studies related to exercise and health sciences and follow the same general criteria applying to other articles in Pensar en Movimiento.